Juvenile scoliosis as the first manifestation of syringomyelia associated with Chiari malformation type I - Julieta Bitler; Clara Ceriani-Cernadas; Nicolas A. Montivero; Alfredo Eymann (Permanyer, 2023)
Background: Scoliosis is a spinal deformity that usually manifests as a structural curve determining a variable deformity of the trunk. According to some published series, 4 to 26% of scoliosis initially classified as idiopathic show neurological alterations when studied with nuclear magnetic resonance, such as syringomyelia and Chiari malformation, among the most frequent. Chiari malformations are characterized by descending herniation of the cerebellar tonsils, brainstem, and IV ventricle into the spinal canal. Case report: We present the case of a patient whose first symptomatic manifestation was early-onset scoliosis. The overlapping of some physical examination signs, such as postural lateralization and scoliosis, reinforced the active suspicion of neuroaxis alterations. Conclusions: Early childhood-onset scoliosis should raise a high degree of suspicion for association with neuro-spinal diseases. Although the frequency of Chiari malformation is low, its early approach could reduce the progression of associated comorbidities. An early detection could change the prognosis of the disease.